Hypolipidemic Effect of Fermented Soymilk Related with Lactic Acid Bacteria in Feaces - Darimiyya Hidayati1,3, Soetjipto2 , Annis Catur Adi1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The problem of obesity is a global problem that is being faced in the world. One of the precautions taken isfunctional food. Fermented soy milk is a functional food that has a hypolipidemic effect. The purpose of thisstudy was to analyze the relationship between the hypolipidemic effect of fermented soymilk and the contentof lactic acid bacteria in animal experiments. The results showed that the provision of fermented soymilkand unfermented soymilk could increase the total content of lactic acid bacteria in rat feaces. This is in linewith the decrease in total blood cholesterol levels in rats. Giving soy milk and fermented soymilk increasesthe total lactic acid bacteria in feaces thereby increasing cholesterol secretion in feaces